Phenolic Compounds and antioxidant activity in extracts of four Oregano species - Bernarda Nohemy Rivas Pérez (Revista Técnica de la Facultad de Ingeniería, Universidad del Zulia, 2017)
The objective of the research was to determine the content of phenolic compounds and antioxidant activity in each extract of oregano. The extracts were obtained using two methods (passive maceration and Soxhlet extraction), with three mixtures of solvents of different polarities methanol-water at 75-25% ethanol-water at 75-25% and hexane-methanol 50-50%. The passive maceration method using methanol-water at 75-25% presented the highest percentage of yield of 24-31.45 and the best results in the physicochemical analysis and microbiological analysis according to the technical norm COVENIN 1539-83. Oregano extract showed higher concentrations of total polyphenols were Lippia origanoide (Verbenaceae) species followed by the Origanum vulgare (Lamiaceae) species whit 475 and 113 mgAG / g dried oregano, respectively and the smaller was species Plectranthus amboinicus (Lour) 17.1 mgAG / g. The highest antioxidant activity was to L. origanoide (2.26 eqmmoles TROLOX / mg) followed the O. vulgare (1.96 eqmmoles TROLOX / mg) for the ABTS method and (1.88 and 1.2) eqmmoles TROLOX / mg extract for the method DPPH. The less antioxidant activity obtained was species Plectranthus for both methods, so that obtained was a direct relation between phenolics and antioxidant activity with an R2 of 0.98.